2021
DOI: 10.1007/s13577-020-00470-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MAFG-AS1 regulates miR-125b-5p/SphK1 axis to promote the proliferation, migration, and invasion of bladder cancer cells

Abstract: MAFG-AS1 is an oncogenic lncRNA in multiple types of cancer. However, its role in bladder cancer (BC) remains unclear. The present study aimed to investigate the function of MAFG-AS1 in BC. BC and paired non-tumor tissues were collected. Two BC cell lines HT01197 and HT-1376 were used. Dual luciferase activity assay, RT-qPCR, western blot, CCK-8, transwell invasion assay, and wound healing assay were performed. We found that MAFG-AS1 was significantly up-regulated in BC tissues and predicted a poor survival ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In addition, we observed that SGMS2 was a risk factor by univariate Cox analysis, and the expression of SGSM2 was negatively correlated with drug sensitivity to Tamoxifen. Sphingosine kinase 1 (SPHK1) can phosphorylate sphingosine to form sphingosine-1-phosphate, which plays critical roles in the regulation of cancer cell proliferation and survival in different types of cancer (36). Our study demonstrated that the increased expression of SPHK1 and SPHK1 was a prognostic biomarker in bladder cancer.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we observed that SGMS2 was a risk factor by univariate Cox analysis, and the expression of SGSM2 was negatively correlated with drug sensitivity to Tamoxifen. Sphingosine kinase 1 (SPHK1) can phosphorylate sphingosine to form sphingosine-1-phosphate, which plays critical roles in the regulation of cancer cell proliferation and survival in different types of cancer (36). Our study demonstrated that the increased expression of SPHK1 and SPHK1 was a prognostic biomarker in bladder cancer.…”
Section: Discussionmentioning
confidence: 82%
“…HOTAIR promotes the proliferation, migration, and invasion of BCa cells by regulating CCNJ and inhibiting miRNA-205 [ 116 ]. MAFG-AS1 regulates the miR-125b-5p/SphK1 and the miR-143-3p/COX-2 axes to promote the proliferation, migration, and invasion of BCa cells [ 117 , 118 ]. SPRY4-IT1 sponges miR-101-3p to promote the proliferation, migration, and invasion of BCa cells by upregulating EZH2 [ 119 ].…”
Section: Invasion Migration and Metastasismentioning
confidence: 99%
“…LncRNA PCAT1 can interact with DKC1 to activate the VEGF/AKT/Bcl-2/caspase9 pathway, thereby regulating non-small cell lung cancer (NSCLC) cell proliferation, invasion, and apoptosis ( Liu et al, 2021 ). A variety of lncRNAs have been reported to play critical role in BCa biology, including lncRNA MAFG-AS1, lncRNA SLC16A1-AS1 and lncRNA SNHG1 ( Tang et al, 2021 ; Logotheti et al, 2020 ; Xu et al, 2020 ). However, the role of lncRNAs in BCa are relatively unknown, specifically that of lncRNA GTF2IRD2P1.…”
Section: Introductionmentioning
confidence: 99%